Perancangan Enterprise Architecture Dengan Menggunakan TOGAF Pada PT Sejahtera Usaha Bersama - Pandu Prawira Negara; Erwin Sutomo; Valentinus Roby Hananto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT Sejahtera Usaha Bersama is one of the largest timber manufacturer in Indonesia which produces wood such as plywood and blockboard. PT Sejahtera Usaha Bersama have has information systems to support the business needs of the company on the production, but at the moment the application of information technology systems only consider immediate needs and allows the application of information systems overlap each other and their sub-systems are different from each other. These conditions make the information system can not be used as expected. Problems arising in the company, especially in the production of one constrained by the lack of monitoring of the production machine, so that when the damage occurred can inhibit the production process in the company. In the production itself there are other problems such as the data is not centralized, resulting in data redundancy and data security is reduced. In the production also does not have adequate application to support activities such as: monitoring production machines and check the quality of the product, resulting in a process for machine maintenance can not be monitored well, and the process of product quality checks are still susceptible to human error. The lack upgraded of the hardware such as computers also affects the enterprise, resulting in disruption of data management processes. Based on these issues, then an analysis using Enterprise Architecture is conducted. With Enterprise Architecture, the issues raised in the company can be analyzed in each phase of TOGAF ADM and then generates proposed improvements of each phase. The results of analysis TOGAF ADM is an IS / IT blueprint that contains five documentss, namely architecture business architecture, information systems architecture (application architecture and data architecture) and technology architecture. IS / IT Blueprint will later be used as reference when the company wants to develop the current IS / IT.